The duration of intestinal immunity after an inactivated poliovirus vaccine booster dose in children immunized with oral vaccine: a randomized controlled trial - John,J; Giri,S; Karthikeyan,AS; Lata,D; Jeyapaul,S; Rajan,AK; Kumar,N; Dhanapal,P; Venkatesan,J; Mani,M; Hanusha,J; Raman,U; et al. (Journal of Infectious Diseases, 2016)
Background.In 2014, 2 studies showed that inactivated poliovirus vaccine (IPV) boosts intestinal immunity in children previously immunized with oral poliovirus vaccine (OPV). As a result, IPV was introduced in mass campaigns to help achieve polio eradication.Methods.We conducted an open-label, randomized, controlled trial to assess the duration of the boost in intestinal immunity following a dose of IPV given to OPV-immunized children. Nine hundred healthy children in Vellore, India, aged 1–4 years were randomized (1:1:1) to receive IPV at 5 months (arm A), at enrollment (arm B), or no vaccine (arm C). The primary outcome was poliovirus shedding in stool 7 days after bivalent OPV challenge at 11 months.Results.For children in arms A, B, and C, 284 (94.7%), 297 (99.0%), and 296 (98.7%), respectively, were eligible for primary per-protocol analysis. Poliovirus shedding 7 days after challenge was less prevalent in arms A and B compared with C (24.6%, 25.6%, and 36.4%, respectively; risk ratio 0.68 [95% confidence interval: 0.53–0.87] for A versus C, and 0.70 [0.55–0.90] for B versus C).Conclusions.Protection against poliovirus remained elevated 6 and 11 months after an IPV boost, although at a lower level than reported at 1 month.